Distally Based Medial Hemisoleus Muscle Flap: Anatomic and Angiographic Study of 18 Lower Limbs. Issue 1 (July 2017) - Bourdais-Sallot, Aurélie; Pare, Arnaud; Herard, Camille; Duclert-Bompaire, Marine; Pucheux, Julien; Terrier, Louis-Marie; Goga, Dominique; Forme, Nathalie; Quignon, Richard
Abstract : Background: The distally based medial hemisoleus (MHS) flap was found useful for repairing soft-tissue defects of the lower third of the leg; however, its reliability is controversial. We used a combination of static and dynamic techniques to investigate the vascular supply of distally based MHS muscle flaps to better establish their use in repair of lower-third leg defects. Methods: We performed an anatomic study of 18 cadaver legs. For 6 legs, we performed dynamic angiography, which allowed for obtaining MHS muscle radiographs after pulsed injection of contrast medium in distal pedicles. Results: The mean length of MHS muscle was 25.4 cm, the mean width was 6.9 cm, and the mean surface area was 87.5 cm 2 . A mean of 3 distal posterior tibial vascular pedicles was directly connected to this medial subunit. These pedicles were present in all 18 cadaver legs. We observed complete opacification of the 6 MHS muscles through distal pedicles. Radiography revealed opacification of a vascular path from 1 distal pedicle to 1 proximal vascular pedicle of the MHS muscle. The mean level of this main distal pedicle was 14.5 cm to the tip of the medial malleolus. The level was at 38.2%, on average, from the bottom of the entire tibia. Conclusions: The distally based MHS muscle flap has constant blood supply, so it could be a useful flap to repair soft-tissue defects of the lower third of the leg. Moreover, knowledge of the average location of the main distal pedicle can help in increasing the use of the distally based MHS flap.